2023
DOI: 10.33828/sei.v34.i1.3
|View full text |Cite
|
Sign up to set email alerts
|

How is Mendelian genetics taught in Malawi?

Abstract: Understanding genetics, an important topic in the study of biology, is critical for scientific literacy in agriculture, health, and forensic investigations. However, it has been observed that teachers find genetics difficult to teach and pupils do not perform well in it. Teachers can use expository teaching or active learning methods, but the secondary school curriculum in Malawi advocates the latter. The aim of this study was to find out how genetics is taught and how teachers justify their choice of method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Findings another study by Altinyelken and Hoeksma (2021), on use of active teaching and learning strategies to improve learning outcomes in secondary schools in Malawi reveal that participants viewed use of active learning strategies positively and as beneficial to students. In addition, a study by Mbano, Chitundu, and Nampota (2023) on strategies used by teachers concluded that teachers regularly used active learning methods of questions and answer. Molande, Mtemangâ, Chikasanda, et al (2017) also investigated use of problem based activities to teach revealed that problem based learning activities are an effective approach hence recommended for teaching.…”
Section: Empirical Evidence On the Use Of Elaboration Strategiesmentioning
confidence: 99%
“…Findings another study by Altinyelken and Hoeksma (2021), on use of active teaching and learning strategies to improve learning outcomes in secondary schools in Malawi reveal that participants viewed use of active learning strategies positively and as beneficial to students. In addition, a study by Mbano, Chitundu, and Nampota (2023) on strategies used by teachers concluded that teachers regularly used active learning methods of questions and answer. Molande, Mtemangâ, Chikasanda, et al (2017) also investigated use of problem based activities to teach revealed that problem based learning activities are an effective approach hence recommended for teaching.…”
Section: Empirical Evidence On the Use Of Elaboration Strategiesmentioning
confidence: 99%